Metabolic responses to metal pollution in shrimp Crangon affinis from the sites along the Laizhou Bay in the Bohai Sea. Issue 1 (15th December 2016) - Xu, Lanlan; Ji, Chenglong; Zhao, Jianmin; Wu, Huifeng
Abstract: Marine environment in the Laizhou Bay is potentially contaminated by metals from industrial discharges. In this study, metal concentrations in shrimps Crangon affinis indicated that two typical sites (S6283 and S5283) close to Longkou and Zhaoyuan cities along the Laizhou Bay have been contaminated by metals, including Cd, As, Cu, Ni, Co, and Mn. In particular, Cd and As were the main metal contaminants in S6283. In S5283, however, Cu was the most important metal contaminant. The metabolic responses in the shrimps indicated that the metal pollution in S6283 and S5283 induced disturbances in osmotic regulation and energy metabolism and reduced anaerobiosis, lipid metabolism, and muscle movement. However, alteration in the levels of dimethylglycine, dimethylamine, arginine, betaine, and glutamine indicated that the metal pollution in S5283 induced osmotic stress through different pathways compared to that in S6283. In addition, dimethylamine might be the biomarker of Cu in shrimp C. affinis . Highlights: The S6283 and S5283 sites were polluted by metals, such as Cd, As and Cu. Metal pollution caused multiple biological effects in shrimp C. affinis . Metal pollution in two sites induced osmotic stress via different pathways.